Spatial Analysis Of Buffalo Development In Brebes Regency - Nanang Nur Rozaq; Mochamad Sugiharto (Jurnal READ (Research of Empowerment and Development), 2020)
The study on spatial dimension of buffalo development in Brebes is intended to (1) analyze the regional shifting patterns of buffalo development within a period of 5 years (2012-2016) and (2) to identify the relationship between the number of farmland areas and the population of buffalo in Brebes Regency. This research employs a secondary data analysis method by utilizing the available data analyzed using a spatial analysis. Location Quotient (LQ) analysis is conducted to analyze the regional shifting patterns of buffalo followed with a product moment correlation analysis to identify the relationship between the number of farmland areas and the population of buffalo livestock. The results show that the buffalo population is related to the number of ​​rice plant areas (P <0.05) as well as that of the peanut plant areas (P <0.01). For the last 5 years (2012-2016), there is no regional shifting pattern in the center for buffalo development in Brebes Regency. The centralization of buffalo develoment in Brebes Regency is located in Salem, Bumiayu, Sirampog, Tonjong, Larangan and Songgom sub-district